2021
DOI: 10.3389/fmed.2021.617068
|View full text |Cite
|
Sign up to set email alerts
|

Professional-Grade TCA-Lactic Acid Chemical Peel: Elucidating Mode of Action to Treat Photoaging and Hyperpigmentation

Abstract: Chemical peeling is usually performed by dermatologists, plastic surgeons, and aestheticians for the treatment of photo-aged skin, dyspigmented skin, skin prone to acne eruption, and pre-cancerous skin lesions, etc. In this research paper, we report our investigative findings to understand the mode of action of a commercial professional chemical peel to treat hyperpigmented and photoaged skin. In the in-vitro experiments, we found that the peel inhibits enzymes that are responsible for degradation of collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…It showed that the peels were able to inhibit tyrosinase, collagenase and elastase activity in in-vitro experiments. Further, an increased expression of COL1A, COL3B, elastin and fibronectin genes were shown to occur when peel solution was used for 3D human skin model [115]. Another study compared the efficacy of AHA-ReT cream (double conjugated retinoid cream) with 1% retinol cream and 0.025% Tretinoin cream for treatment of photoaging.…”
Section: Other Compounds Used For Treatment Of Photoaged Skinmentioning
confidence: 99%
“…It showed that the peels were able to inhibit tyrosinase, collagenase and elastase activity in in-vitro experiments. Further, an increased expression of COL1A, COL3B, elastin and fibronectin genes were shown to occur when peel solution was used for 3D human skin model [115]. Another study compared the efficacy of AHA-ReT cream (double conjugated retinoid cream) with 1% retinol cream and 0.025% Tretinoin cream for treatment of photoaging.…”
Section: Other Compounds Used For Treatment Of Photoaged Skinmentioning
confidence: 99%
“…chemicals such as pyruvic acid, 5 acrylic acid, 6 propionic acid, 7,8 acetaldehyde, 9 alanine, 10 and glycerol carbonate. 11 It has also been used to remove hyperpigmentation 12 and to extend the shelf life of foods. 13 LA can be produced on a large scale starting with glycerol, which is a waste product of the continuously increasing biodiesel production through biomass conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid (2-hydroxypropanoic acid, LA) is an extensively used chemical in a wide range of industrial applications including foods, 1 drugs, 2 cosmetics, 3 medication, 4 and the production of chemicals such as pyruvic acid, 5 acrylic acid, 6 propionic acid, 7,8 acetaldehyde, 9 alanine, 10 and glycerol carbonate. 11 It has also been used to remove hyperpigmentation 12 and to extend the shelf life of foods. 13 LA can be produced on a large scale starting with glycerol, which is a waste product of the continuously increasing biodiesel production through biomass conversion.…”
Section: Introductionmentioning
confidence: 99%
“…TCA has keratocoagulant action and is therefore considered a gold standard peeling agent by some dermatologists. These two active ingredients work synergistically when used together, and because of this synergy, a lower dose of TCA is needed 4 …”
Section: Introductionmentioning
confidence: 99%
“…These two active ingredients work synergistically when used together, and because of this synergy, a lower dose of TCA is needed. 4 There are some studies showing the effect of chemical peeling on melanin, collagen, elastin, epidermal and dermis thickness. 4 However, these studies either used human skin explants for the chemical peel treatment 4 or used the classical invasive punch biopsy and histological staining approach to observe changes.…”
mentioning
confidence: 99%